Die Biokraftstoff-Nachhaltigkeitsverordnung: Ein erster Schritt in eine nachhaltige Bioenergiepolitik oder ein weiteres Stück Bürokratie?; The Biofuel Sustainability Regulation: A First Step towards a Sustainable Bioenergy Policy, or rather, another Piece of Red Tape? - Stefan Busse; Bernhard Brum̈mer (German Journal of Agricultural Economics (GJAE), 2011)
– At 1 January 2010, the German Biofuel Sustainability Regulation which implements the requirements set out by EU directive 2009/28/EC entered into force. For the first time, these regulations define legal sustainability standards for biomass used for energy production. The main criteria are a minimum level of greenhouse gas savings and the avoidance of negative environmental impacts. However, the analysis of these regulations casts doubt on the achievability of its targets: Rather than the desired improvement in the sustainability of biomass production, increased market segmentation is the likely outcome. A broader regulation is constrained both by its practicability (e.g. in the case of quantification of indirect effects) and by the legal framework of the WTO (use of trade distorting measures). Hence, the attempt to cover general environmental aspects and particular biofuel related sustainability aspects within one single regulatory framework seems an unpromising avenue towards improved sustainability of biomass production.
Keywords: 330; Bioenergie; Biokraftstoff; Energieerzeugung; Dauerhafte Entwicklung; Emissionsreduktion; Förderung erneuerbarer Energien; Nachhaltigkeit; Treibhausgas-Emissionen; Wirkungsanalyse; Deutschland